ANALISIS PERBANDINGAN PENGGUNAAN JUAL BELI ONLINE DAN JUAL BELI OFFLINE OLEH MAHASISWA INSTITUT AGAMA ISLAM SAHID BOGOR PADA MASA PANDEMI COVID-19 - Abad, Geopani; Trihantana, Rully; Kusumaningrum, Ria (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
The online purchasing system and the direct purchase system are tools used by the public in making product purchases. Purchase by online is a form of percentage and promotion, marketing of goods and services using certain media such as newspapers, magazines, radio, television, billboards, brochures, social media, internet and others, while direct buying is a situation when a seller offers/ selling its products directly to consumers (both individual consumers and businesses). Interest that arises from within the consumer will have an effect on increasing the number of purchases, because it will increase consumer purchasing decisions to buy goods. The main purpose of this study was to determine the effect of differences between online purchases and direct purchases on consumer buying interest in purchasing decisions. This research was conducted with a quantitative method using an online questionnaire. The population in this study were students who had made online and direct purchase transactions. The number of respondents from this study were 132 respondents. The data analysis technique used is SPSS software. The test results show that there is significant difference between the use of selling online and selling directly during the covid-19 pandemic for INAIS Bogor students